Risk-based triage strategy by extended HPV genotyping for women with ASC-US cytology - Xuan Rao; Yue-Han Wang; Rui-Zhe Chen; Qian-Qian Wu; Xiao-Fei Zhang; Yun-Feng Fu; Xin-Yu Wang; Xiao Li (Annals of Medicine, 2025)
Objective We attempted to evaluate the immediate high-grade squamous intraepithelial lesion-cervical intraepithelial neoplasia grade 2/3 or worse (HSIL-CIN2+/3+, hereafter referred to as CIN2+/3+) risk of specific human papillomavirus (HPV) genotype and form the precise risk-based triage strategy for atypical squamous cells of undetermined significance (ASC-US) women.Methods The clinical data of ASC-US women who underwent HPV genotyping testing and colposcopy were retrospectively reviewed. The distribution and CIN2+/3+ risks of specific HPV genotype were assessed by three approaches. The risk-based triage strategy was further established, and its efficacy in detecting CIN2+/3+ was estimated.Results Totally, 5553 ASC-US women including 3648 HPV-positive and 1905 HPV-negative were analysed. CIN2+/3+ were 662/319 cases, including 639/306 HPV-positive and 23/13 HPV-negative women. HPV16, HPV52, HPV58 and HPV18 were always among the top 5 ranking genotypes, no matter in HPV-positive women or in HPV-positive CIN2+/3+ cases. HPV16 and HPV33 carried the highest risk, while HPV73 and 26 carried the least risk for CIN2+/3+. Based on the immediate CIN2+/3+ risk of specific HPV genotype, 18 HPVs were divided into three risk-stratified groups. Only women infected with HPVs included in group A were necessary for immediate colposcopy. Compared with conventional strategy, this new risk-based strategy not only had higher specificity (CIN2+: p = .00; CIN3+: p = .01) and positive predictive value (CIN2+: p = .00; CIN3+: p = .03) for detecting CIN2+/3+, but also needed fewer colposcopies to identify each CIN2+/3+.Conclusions A new triage strategy for ASC-US women was successfully constructed based on CIN2+/3+ risks of 14 high-risk and 4 intermediate-risk HPVs, which could significantly reduce unnecessary colposcopies.